2012
DOI: 10.9715/kila.2012.40.4.090
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on the Recognition of Urban Agriculture between Urban Farmers and Public Officials

Abstract: T h ea i m o ft h i ss t u d yi st ob ea b l et ou n d e r s t a n dt h ep r o b l e msw i t h i nt h eu r b a na g r i c u l t u r ep o l i c yp r o mo t e db yt h eG o v e r n me n ta n dl o c a la u t o n o mo u se n t i t yb a s eo nt h ec o mp a r i s o no ft h ec o n s c i o u s n e s so ft h eu r b a na g r i c u l t u r eb e t w e e n u r b a nf a r me r sa n dp u b l i co f f i c i a l sa n dt oi n q u i r ei n t ot h ef u r t h e rr e v i t a l i z a t i o ns c h e mei nt h ee n d . F o rt h i sp u r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…These results were similar to those of Park et al (2012) that urban agriculture is correlated with vitalizing local economy and agriculture, and thus income level seems to be one of the most important factors of the recognition of vitalizing agriculture connected with local agriculture.…”
Section: Comparison Of Income Level and Socially Sustainable Effect (supporting
confidence: 88%
See 1 more Smart Citation
“…These results were similar to those of Park et al (2012) that urban agriculture is correlated with vitalizing local economy and agriculture, and thus income level seems to be one of the most important factors of the recognition of vitalizing agriculture connected with local agriculture.…”
Section: Comparison Of Income Level and Socially Sustainable Effect (supporting
confidence: 88%
“…Urban agriculture was initiated as a measure to secure food resources and provide safe food for urban residents, but recently it has been considered as a major component for sustainable cities for the purposes of addressing urban environmental problems and improving the quality of life of urban residents (Park et al, 2012), rapidly expanding its roles around the world such as restoring urban ecology, securing safe food and utilizing as a leisure activity for urban residents.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Literature review Overall, 15 indicators were derived from our literature review [1,6,7,9,[21][22][23][24][25][26][27][28][29][30][38][39][40][41][42][43][44][45][46], of which 12 were also derived from theoretical reviews. The following three indicators were derived solely from the literature review.…”
Section: Indicator Derivationmentioning
confidence: 99%
“…Soil contamination was chosen as an indicator because contaminated soil is an inappropriate environment for agriculture and requires minimum separation. The "ease of securing cultivation soil" indicator in the category "farming conditions" was selected because different soils are required for cultivating different varieties of crops and because the growth features of herbaceous plants vary with soil conditions [41]. The "ratio of people with high crop-cultivation experience" indicator in the category "resident status" has been considered in numerous studies, including those by Jang et al, and these studies have found that the absence or presence of crop-cultivation experience massively contributed to experiencing and adapting to urban farming [9,42].Analysis of media articles…”
Section: Indicator Derivationmentioning
confidence: 99%
“…Accordingly, studies have been conducted in multiple aspects to activate urban agriculture and improve the system, such as studies on policies to activate and promote urban agriculture for energy independence (Na, 2010), comparison and evaluation of the perception on urban agriculture among urban farmers and public officials (Park et al, 2012), improvement plans for urban planning systems to secure spaces for urban agriculture (Choi, 2014), and valuation of the current state of urban agriculture participation and multifunctionality (Heo and Kwon, 2014).…”
Section: Introductionmentioning
confidence: 99%